INVESTIGATION OF ELECTRICAL AND THERMAL PROPERTIES OF AMINATED POLY (VINYL CHLORIDE)-OXIDIZED MULTIWALLED CARBON NANOTUBE COMPOSITES - HARUNA, HASSAN (Fırat Üniveristesi, 2018)
Carbon Nanotubes (CNTs) are of great demands because of their noble physical properties and many application possibilities that covered a lot of area in nanotechnology. This study is concerned with the preparation and characterization of composites of oxidized MWCNT with aminated PVC. Ranges of 2 %, 5 %, 8 %, and 11 % in weight percentages of oxidized MWCNTs were added to THF solution of aminated PVC containing 10.77 % of amine groups. Sonicated for homogeneity followed by precipitation in ethanol made the final mixing of each concentration. Composites containing oxidized MWCNT in different weight percentages were doped with nanographite in different percentages (1 %, 3 %, 5 %, 8 % and 12% by weight). FT-IR, DSC, TGA, and SEM are used to characterized these composites. The electric properties at different temperatures and frequencies were measured for all composites. It was found that the dielectric constant values of all composites decrease with increasing of the applied field frequency and increase with increasing oxidized MWCNT content. This is due to the decrease in polarization and the dipoles can no longer follow the rapid changes in field direction. However, A.C. conductivities for the all composites increase rapidly with increasing frequency and decrease as the temperature increases. Also its thermal properties is directly proportional to the oxidized MWCNTs contents.

Karbon nanotüpler, fiziksel özelliklerinden ve nanoteknolojide çok fazla alanı kapsayan birçok uygulama olanağı sunduğundan dolayı rağbet görmektedirler. Bu çalışmada poli (vinil klorür)-çok duvarlı karbon nanotüp kompozitlerinin termal ve elektriksel özellikleri incelenmiştir. Ağırlıkça % 2, % 5, % 8 ve % 11 oranlarında karboksilli MWCNT, %10.77 amin grubu içeren aminlenmiş PVC' nin THF içerisinde hazırlanmış çözeltisine eklendi. Bütün kompozitler homojenize olması için sonike edilerek ve ardından etanolde çöktürülürek hazırlandı. Aminlenmiş PVC / % 4, % 8 ve % 12 oranlarında karboksilli MWCNT kompozitleri, sırasıyla %1, %3, %5, %8 ve %11 oranlarında nanografitle doplama yapıldı. Sentezlenen tüm kompozitler FT-IR, DSC, TGA ve SEM ile karekterize edildi. Hem aminlenmiş PVC / karboksilli MWCNT kompozitleri hem de nanografit ile doplanmış kompozitlerin farklı sıcaklık ve frekanslarda dielektrik ölçümleri yapıldı. Aminlenmiş PVC / karboksilli MWCNT kompozitlerinin elektriksel özelliklerinin artan karboksilli MWCNT içeriğiyle arttığı bulundu. Ancak artan freakansla azaldığı görülmüştür. Sonuçlar, artan freakansla dielektrik kaybının azaldığını ve A.C iletkenliğinin karboksilli MWCNT' lerin konsantrasyonu ile doğru orantılı olduğunu göstermiştir. Farklı sıcaklık ve frekanslarda doplanmış nanografitlerin elektriksel ölçümleri yapılmış ve nanografitle doplanmış kompozitlerin elektriksel özelliklerinin, nanografit içeriğinin artmasıyla ve frekansla ters orantılı olarak arttığı bulunmuştur. Ayrıca termal özelliklerinin de karboksilli MWCNT ve nanografit oranlarıyla doğru orantılı olduğu tespit edilmiştir.
Aminlenmiş poli (vinil klorür)- oksitlenmiş çok duvarlı karbon nanotüp kompozitlerinin elektrik ve termal ve mekanik özelliklerinin incelenmesi
Keywords: Kimya